2006
DOI: 10.1159/000095303
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cognitive Deficits in Amnestic Mild Cognitive Impairment

Abstract: Objective: To determine if more widespread cognitive deficits are present in a narrowly defined group of patients with the amnestic form of mild cognitive impairment (MCI). Methods: From a larger sample of patients clinically diagnosed as meeting the criteria of Petersen et al. for amnestic MCI, we selected 22 subjects who had Clinical Dementia Rating scores of zero on all domains besides memory and orientation. These MCI subjects with presumably isolated memory impairments were compared to 35 age-matched norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
85
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 59 publications
16
85
1
3
Order By: Relevance
“…In addition, associated complex reduction of the parietal lobe suggested that cognitive impairment may not only have simple memory loss but other brain functions such as motion and sensation function decline. This result is consistent with Krame et al [24] research result. According to above, we deduced: in the same time series, EEG signals shows higher rate of new model in normal elderly people than in cognitive impairment patient, and complexity of the brain acceptance and processing are both higher, so that the brain function is relatively intact.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, associated complex reduction of the parietal lobe suggested that cognitive impairment may not only have simple memory loss but other brain functions such as motion and sensation function decline. This result is consistent with Krame et al [24] research result. According to above, we deduced: in the same time series, EEG signals shows higher rate of new model in normal elderly people than in cognitive impairment patient, and complexity of the brain acceptance and processing are both higher, so that the brain function is relatively intact.…”
Section: Discussionsupporting
confidence: 93%
“…It measures procedural skills that are likely mediated through executive abilities, whereas task 4a measures factual knowledge and is likely mediated by long-term semantic memory. These procedural declines are consistent with the executive function deficits exhibited by patients with amnestic MCI, [23][24][25][26] and the strong ties between executive function and functional abilities. 18,[27][28][29][30][31][32][33] Checkbook management (domain 4) item responses were further analyzed to describe common errors made by MCI converter participants.…”
Section: Changes In Task and Item Level Performance On Check-supporting
confidence: 75%
“…Sperling et al [37] state that cognitive decline in non-memory domains often accompanies declines in episodic memory which highlights the need to identify neuropsychological tests that will aid in identifying individuals in the earliest stages of cognitive decline. This statement is supported by longitudinal results from Johnson et al [38] and Small and Bäckman [39], showing that decline in cognitive domains other than memory is detectable in preclinical AD, and also by Kramer et al [40] and Ribeiro et al [41] who also demonstrated that non-memory domains show decline in individuals with MCI.…”
Section: Discussionmentioning
confidence: 62%